Strategi Pemasaran Dalam Upaya Peningkatan Penjualan Makanan dan Minuman Luwih Cafe Dalung Kabupaten Badung - Wirawan, I Ketut; Dewi, Luh Komang Candra; Saharjo, Sulistyoadi Joko (Universitas Triatma Mulya, 2025)
In developing a restaurant, a marketing strategy is essential to win the competition among businesses. The large number of competitors in the Dalung area poses a challenge for managers to increase sales of food and beverages. Effective marketing strategies are the key to the success of hospitality businesses in the current era of digitalization. The purpose of this study is to identify the internal and external marketing factors and determine the appropriate marketing strategies for the products offered by Luwih Cafe Dalung in Badung Regency. This study uses a qualitative approach. Data collection techniques such as observation, interviews, and literature review were used. The analysis technique used is qualitative descriptive analysis using SWOT analysis. The results of this study indicate that there are internal and external factors of Luwih Café Dalung and alternative strategies to increase food and beverage sales. Four strategies are formulated, such as (1) SO strategy by providing a variety of healthy contemporary menus, organizing family events at affordable prices, and online offers through media and online ordering platform applications, (2) WO strategy, namely promoting specialty foods and conducting effective and efficient menu analysis, (3) ST strategy, which can be applied by expanding the menu with vegan options to provide more variety for visitors with families, implementing a membership program, and providing a suggestion box to collect visitor complaints. (4) is the WT strategy by providing training to staff and evaluating visitor input and market demand. It is hoped that these suggested alternative strategies will increase food and beverage sales at Luwih Café Dalung.